Sposoby skutecznej realizacji strategii - Kaleta, Andrzej (Effective Strategy Implementation, 2008)
The paper Effective Strategy Implementation focuses on the strategy implementation process, which, although being a crucial stage in strategic management, usually results in failure. The condition for effective strategy implementation is emphasizing this stage in strategic management procedure so that it is perceived as an integral and central part, rather than a separate element. The success of strategy implementation depends on the ability to communicate strategy, prepare implementation plans, delegate tasks and control the development processes.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 128-138